(untitled) (Journal of Applied Learning and Teaching, 2024)
Due to the growing use of chatbots such as ChatGPT and Google Gemini in educational contexts, there is an increasing interest in exploring the perception of students accepting and using Gemini as a unique and effective platform in their educational activities. This research examines the perceptions of Saudi Arabian higher education students towards accepting and using Gemini for academic purposes. Drawing upon the Unified Theory of Acceptance and Use of Technology (UTAUT), a self-administered questionnaire was used; 400 forms were completed and validated for analysis from seven public universities in Saudi Arabia. Structural Equation Modeling (SEM) using SmartPLS was adopted to examine the research hypotheses. The major findings agree with UTAUT and prior studies to some extent in terms of the positive influence of performance expectancy (PE), effort expectancy (EE), and social influence (SI) on students’ intention to utilize Gemini, as well as the influence only of PE on the actual use of Gemini. However, the findings differ from previous research regarding the influence of facilitating conditions (FC) on students’ intention to utilize Gemini; the results were significant but negative. In addition, EE, SI, and FC did not directly affect the actual use of Gemini. These results were due to the lack of valid resources, assistance, and guidance from educational authorities and external sources about the ideal use of Gemini. Furthermore, the findings exposed that BI partially mediates the connection between PE and Gemini’s actual usage and fully mediates between EE and SI and Gemini’s actual usage.